2017
DOI: 10.5505/respircase.2017.93585
|View full text |Cite
|
Sign up to set email alerts
|

A new definition: Combined pulmonary fibrosis and emphysema syndrome

Abstract: ÖzetKombine pulmoner fibrozis ve amfizem sendromu (KPFA), kendine özgü klinik bulguları olan ve radyolojik olarak üst lob amfizemi ve alt lob fibrozisi ile karakterize yeni tanımlanan bir sendromdur. Hastalık iyi bilinmediği için yeterince tanı konulamamaktadır. Progresif nefes darlığı şikayetiyle başvuran, 60 paket/yıl sigara öyküsü olan erkek hastanın çekilen toraks tomografisinde KPFA sendromuna özgü üst loblarda amfizem ve alt loblarda fibrozis izlendi. Hastalığın bir diğer önemli özeliği olarak FEV1 kıs-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Recently, cases of CPFE have been published in the literature. [6,7] CPFE is a newly identified syndrome characterized by specific clinical findings and radiological identification with upper lobe emphysema and lower lobe fibrosis. Since the disease is not well known, diagnosis remains inadequate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, cases of CPFE have been published in the literature. [6,7] CPFE is a newly identified syndrome characterized by specific clinical findings and radiological identification with upper lobe emphysema and lower lobe fibrosis. Since the disease is not well known, diagnosis remains inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that 35% of all idiopathic pulmonary fibrosis (IPF) patients are actually cases of CPFE, and in current studies, high rates of emphysema (8-50%) have been reported in patients whose high-resolution computed tomography (HRCT) revealed the presence of pulmonary fibrosis [2,10,11] It is important to be able to define this disease, as the clinical course of CPFE differs from that of IPF. [7] CPFE syndrome is radiologically characterized by emphysema in the upper lobes and interstitial fibrosis in the lower lobes. In the upper lobes, paraseptal emphysema is more frequent, but centrilobular emphysema and bullous changes may be also seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation